„Jest wielu Kainów pośród nas”. Polski wymiar sprawiedliwości a Zagłada, 1944–1956 - Andrew Kornbluth (Zagłada Żydów)
From 1944 to 1960, Poland held at least 32 000 trials for war crimes and collaboration; in particular, those records generated by the investigations of crimes against Jews have been the basis for ground-breaking studies of the Holocaust in Poland for over a decade now. While Poland was a society without a Quisling, these studies have shown that the country was still very much part of a pan-European continuum in which local people took part in ethnic cleansing inspired by the Nazi occupation. The question remains, then, of how effective the postwar judicial process against the collaborators was. This article makes use of the records of over 450 trials of accused collaborators, held between 1946 and 1949 at the district courts of Warsaw and Siedlce, of which about one-third are cases involving crimes against Jews. These trials are used as the starting point for a wider discussion of post-war justice in Poland.